Essentials of english grammar (english plus) - Alcantara, Rebecca D.; Cabanilla, Josefina Q M.A (Quezon City, 1999)
Essentials of English Grammar brings the insights of modern grammarians to the perennial concerns of the English classroom. The major concern in this book is with the grammar of English
Keywords: English language - exercises; English language - Grammar